Transcriptional, Behavioral and Biochemical Profiling in the 3xTg-AD Mouse Model Reveals a Specific Signature of Amyloid Deposition and Functional Decline in Alzheimer’s Disease - Yin, Wencheng; Cerda-Hernández, Navei; Castillo-Morales, Atahualpa; Ruiz-Tejada-Segura, Mayra L.; Monzón-Sandoval, Jimena; Moreno-Castilla, Perla; Pérez-Ortega, Rodrigo; Bermudez-Rattoni, Federico; Urrutia, Araxi O.; Gutiérrez, Humberto (Frontiers in Neuroscience, 2020)
Alzheimer’s disease (AD)-related degenerative decline is associated to the presence of amyloid beta (Aβ) plaque lesions and neuro fibrillary tangles (NFT). However, the precise molecular mechanisms linking Aβ deposition and neurological decline are still unclear. Here we combine genome-wide transcriptional profiling of the insular cortex of 3xTg-AD mice and control littermates from early through to late adulthood, with behavioural and biochemical profiling in the same animals to identify transcriptional determinants of functional decline specifically associated to build-up of Aβ/NFT deposits. Differential expression analysis revealed differentially expressed genes (DEGs) in the cortex long before observed onset of behavioural symptoms in this model. Using behavioural and biochemical data derived from the same mice and samples, we found that down but not up-regulated DEGs show a stronger average association with learning performance than random background genes in control not seen in AD mice. Conversely, these same genes were found to have a stronger association with Aβ deposition than background genes in AD but not in control mice, thereby identifying these genes as potential intermediaries between abnormal Aβ/NFT deposition and functional decline. Using a complementary approach, gene ontology analysis revealed a highly significant enrichment of learning and memory, associative, memory and cognitive functions only among down-regulated, but not up-regulated, DEGs. Our results demonstrate wider transcriptional changes triggered by the abnormal deposition of Aβ/NFT occurring well before behavioural decline and identify a distinct set of genes specifically associated to abnormal Aβ protein deposition and cognitive decline.